A Survey on the Growth and Development of MSME in Tamil Nadu - Raj, Taflin S; R, Radhika (Recent Research Reviews Journal, 2024)
Micro Small and Medium Enterprise (MSME) provides a vital contribution towards financial expansion and advancement in the development of the economy. This system provides an environment for nurturing various innovative ideas and creativity. This in turn paves the way to create jobs and uplift the socio-status of the livelihood, and subsequently regarded as the world’s economic foundation. Micro, Small, and Medium Enterprises (MSMEs) assist industries as supplementary units, making a significant contribution to the country’s total growth in industry. These industries produce, manufacture, and deal with various products and commodities. When compared with the year 2022, there is a 29% increase in the commercial sector as well as a 20% increase in the overall supply sector in lakhs, which leads to an increase of 12% in crores for MSME growth throughout India in 2023. This research work puts forth the several implications of MSME in the development of MSME in Tamil Nadu